Direct and moderating effects of COVID-19 on cultural tourist satisfaction - María Dolores Sánchez-Sánchez; Carmen de Pablos Heredero; José Luis Montes Botella (European Research on Management and Business Economics (ERMBE), 2024)
This paper proposes a model to determine the direct and moderating effects of COVID-19 on the overall satisfaction of cultural tourists with the heritage destination visited. The hypotheses put forward in the model have been tested employing non-linear structural equation models (SEM), estimated with data from the Resident Travel Survey of the National Statistics Institute (NSI), on domestic demand for cultural tourism in Spain. The data analyzed covers both a pre-covid and pandemic period, from January 2019 to September 2021. The results confirm that COVID-19 significantly impacted the decrease in cultural tourists' satisfaction with the visit. It highlights the negative relationship between cultural tourists' socioeconomic profile and satisfaction. This research provides knowledge on the impact of COVID-19 on the behavior of cultural tourists, with practical implications for the design of tourism policies for the promotion and marketing of heritage destinations through differentiated marketing that increases satisfaction for this demand segment in crisis scenarios.
Keywords: C3; M3; Z3; 650; COVID-19; Cultural tourism; Structural equations; Tourist satisfaction